1976
DOI: 10.1111/j.1600-0528.1976.tb00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of an amine fluoride gel and acidulated phosphate fluoride gel

Abstract: This study compared caries inhibition in children by an amine fluoride and an acidulated phosphate fluoride when administered in a topically applied gel. In addition, the effects of applying amine fluoride daily and weekly were compared. Four hundred and sixty-eight children, ages 6 to 13, were randomly assigned to one of five treatment groups and received a total of five, 5-minute treatments. The treatment and interval between each of the five treatments were as follows:(A)acidulated phosphate fluoride daily,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…This difference may be attributed to the younger age of those groups, because it is well known that younger patients react better and can be more easily motivated. The good results of a 31-53% DMFS reduction in clinical studies using only amine fluoride gel [Marthaler et al, 1970;Shern et al, 1976;Franke et al, 1977;Obersztyn and Kolwinski, 1983;Szőke and Kozma, 1989] may be attributed to the lower starting age and longer study duration. The gel probably needs more time to show a statistically significant caries protective effect [Marthaler et al, 1970;Franke et al, 1977;Szőke and Kozma, 1989].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may be attributed to the younger age of those groups, because it is well known that younger patients react better and can be more easily motivated. The good results of a 31-53% DMFS reduction in clinical studies using only amine fluoride gel [Marthaler et al, 1970;Shern et al, 1976;Franke et al, 1977;Obersztyn and Kolwinski, 1983;Szőke and Kozma, 1989] may be attributed to the lower starting age and longer study duration. The gel probably needs more time to show a statistically significant caries protective effect [Marthaler et al, 1970;Franke et al, 1977;Szőke and Kozma, 1989].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials with amine fluoride toothpaste, performed between 1968 and 1995 [Marthaler, 1968[Marthaler, , 1974Patz and Naujoks, 1970;Ringelberg et al, 1979;Cahen et al, 1982;Leous et al, 1995] with a duration of 2.5-7 years, reported reductions in mean DMFT/DMFS of between 7.1 and 35%. Studies with amine fluoride gel [Marthaler et al, 1970;Shern et al, 1976;Franke et al, 1977;Obersztyn and Kolwinski, 1983;Szöke and Kozma, 1989] from 1970 to 1989, with a duration of 1.5-7 years, report caries reductions of between 31 and 53%. In a 7-year clinical study using a combination of amine fluoride products , a 43% reduction in DMFS mean values was found.…”
mentioning
confidence: 99%
“…For example, Ripa [1989] found 36% average caries reduction for the included studies on self-administered fluoride tray application in fluoride-deficient communities. By excluding 'three extreme results: namely those from both treatment groups in the Englander et al study [1967], which have never been confirmed in other independent clinical trials, and one group in the study by Shern et al [1976], which may be an aberration', Ripa [1989] adjusted the effectiveness of self-administered fluoride tray studies in fluoride-deficient communities from the initial 36% into 26%. As a result, self-administered fluoride tray application showed similar caries reductions for fluoride-deficient and fluoridated communities (all approximately 26%).…”
Section: Discussionmentioning
confidence: 99%
“…However, the design of the experiment was selected in order to investigate the effect of acidified gels in a time-lapse fashion. Elmex gelée was chosen in the study, since it has been shown to be an effective agent with respect to caries prevention [Shern et al, 1976].…”
Section: Discussionmentioning
confidence: 99%